UI/UX Design of Waste Management Application Using Design Thinking Method - Saraswati, Devy; Adnan, Fahrobby; Pandunata, Priza (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Anyelir Waste Bank is one of the waste banks assisted by PLN's Jakarta Main Distribution Unit which is located in East Jakarta Regency. Ongoing activities are still carried out manually, resulting in various problems. Therefore, the role of technology is needed to overcome problems related to waste management through scientific media designing the fields of User Interface (UI) and User Experience (UX) by designing waste management applications using design thinking. Design thinking was chosen because it combines priorities based on user needs with appropriate technological capabilities and business needs. Application design is designed on a mobile platform for customers while management is on a website platform. This research produces solutions for application design and usability testing has been carried out. Usability testing according to the ISO 9241-11 standard includes aspects of effectiveness, efficiency and satisfaction. In carrying out usability testing to measure aspects of effectiveness and efficiency using task scenarios, while to measure aspects of satisfaction using System Usability Scale (SUS).